What Is Artificial about Life? - Alessandro Giuliani; Ignazio Licata; Carlo M. Modonesi; Paolo Crosignani (The Scientific World Journal)
The announcement of “Artificial Life” by the Craig Venter group, and the media stir that arose from the news, provoked thoughts about the current technologies in contemporary science and the cultural tension of such projections on the media. The increasingly blurred boundaries between specialist and generalist media, while promising a wider appreciation of scientific discovery, potentially allow unrealistic, ideological claims to dictate scientific research. This is particularly evident in biology, where the pervading paradigm is still dominated by a physically naïve reductionism in which the only relevant causative layer is the molecular one. The reductionist hypothesis is that everything one observes is the result of an underlying molecular mechanism almost independent of the context in which it operates. Molecular mechanisms are often necessarily studied in isolation and therefore operate in unnatural conditions. The mechanistic view of biological regulation implies that we think of genes as intelligent agents. Here we try to critically analyze the motivations behind the spread of such unrealistic simplifications.